2021
DOI: 10.3389/fmicb.2020.610296
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistant Klebsiella pneumoniae ST101 Clone Survival Chain From Inpatients to Hospital Effluent After Chlorine Treatment

Abstract: In this paper we describe the transmission of a multi-drug resistant Klebsiella pneumoniae ST101 clone from hospital to wastewater and its persistence after chlorine treatment. Water samples from influents and effluents of the sewage tank of an infectious diseases hospital and clinical strains collected from the intra-hospital infections, during a period of 10 days prior to wastewater sampling were analyzed. Antibiotic resistant K. pneumoniae strains from wastewaters were recovered on selective media. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…The high proportion of tLST-positive clinical isolates of K. pneumoniae compared to that of K. pneumoniae isolates from other sources suggests that the tLST-mediated resistance to disinfection agents may facilitate persistence in hospitals. A tLST-positive K. pneumoniae isolate from a hospital chlorination tank influent was also resistant to 10 antibiotics ( 49 ). A pattern of higher frequency of the tLST in clinical isolates of C. sakazakii was not observed; however, 73.5% of genomes of clinical isolates of C. sakazakii clinical strains possessed the sHsp20 and clpK genes of the tLST, while only 24.3% of the environmental strains had these genes.…”
Section: Discussionmentioning
confidence: 99%
“…The high proportion of tLST-positive clinical isolates of K. pneumoniae compared to that of K. pneumoniae isolates from other sources suggests that the tLST-mediated resistance to disinfection agents may facilitate persistence in hospitals. A tLST-positive K. pneumoniae isolate from a hospital chlorination tank influent was also resistant to 10 antibiotics ( 49 ). A pattern of higher frequency of the tLST in clinical isolates of C. sakazakii was not observed; however, 73.5% of genomes of clinical isolates of C. sakazakii clinical strains possessed the sHsp20 and clpK genes of the tLST, while only 24.3% of the environmental strains had these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, chemical agents can promote HGT in pathogens and thus contribute to AMR spread (Alotaibi et al, 2017;Lu and Guo, 2021). For example, hospital K. pneumoniae strains harboring numerous ARGs, can become tolerant to chlorine, and can then escape into environment through hospital wastewaters (Popa et al, 2020).…”
Section: Hospital Surfaces and Wastewater Treatmentmentioning
confidence: 99%
“…For example, hospital K . pneumoniae strains harboring numerous ARGs, can become tolerant to chlorine, and can then escape into environment through hospital wastewaters ( Popa et al, 2020 ).…”
Section: Prevention Of Infectionmentioning
confidence: 99%
“…Horizontal gene transfer may be facilitated by the high concentration and diversity of microbial flora of FSTPs via mobile genetic components like plasmids ( 21 , 22 ). It is alarming that, in many studies, the existence of an increasing ratio of ARB was reported both in raw sludge and effluent of the treatment plants in the case of urban sewage ( 23 25 ) as well as hospital effluents ( 26 , 27 ). However, apart from medicinal residues and ARGs, the main focus of faecal sludge recycling was on heavy metals, bacterial pathogens, and organic contaminants.…”
Section: Introductionmentioning
confidence: 99%